ANALISIS KESAMAAN RUMPUN BAHASA BI DAN MALAGASI SEBAGAI ALAT BANTU PROSES PEMBELAJARAN BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) - Dewi Nastiti Lestari N. (MABASAN, 2014)
The promotion of bahasa Indonesia as an international language, as stated in the Article No. 44 of the Law No. 24 of 2009, is indirectly meant to give a wider oppurtunity to introduce bahasa Indonesian to the world through the learning of bahasa Indonesia for foreign learners. This   article is a simple review and a result of action reseach conducted by Nastiti (2010) in the BIPA program of Trisakti University. The result shows that the learners from Madagascar mastered bahasa Indonesian faster than other learners. It is assumed that such progress occurred due to the similarity in the language family, Austronesian language. This article discusses a medium of interaction of bahasa Indonesian for foreign learners through the exploration of the similarities of a language family, i.e between bahasa Indonesian and Malagasi language. Cross linguistics understanding and the learners’ language influenced significantly to the mastery of the target language. This article describes several words in Malagasi language which are derived from loan words from a number of local languages in Indonesia, such as Ma’anyan language (Kalimantan), Malay, Javanese, and South Sulawesi languages. These load words were used as a medium for learning bahasa Indonesian (BIPA) among Madagascar learners. Results of analysis shows thatthere was a number of levels of difficulty pertaining to the structure of the learners’language and the instructional prediction of BIPA learners from Madagascar which benefit for BIPA teachers especially for those who involes in Developing Country Program or other BIPA programs.